2008
DOI: 10.3748/wjg.14.518
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of regional radiotherapy with phosphorus-32 glass microspheres in hepatocellular carcinoma recurrence after hepatectomy

Abstract: Preventive effect of regional radiotherapy with phosphorus-32 glass microspheres in hepatocellular carcinoma recurrence after hepatectomy. World

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Embolization alone is an effective treatment, but application of gel foam can be used to enforce treatment efficacy. 8 Therefore, when rich blood supplies were observed following infusion, 1×1-mm gel foam granules were used during the embolization. Six patients were embolized via hepatic segmental artery, nine Large mass diameter of a single tumor >5 cm, nodules diameter of a single tumor <5 cm, diffuse diameter of a single tumor <3 cm with multiple tumors, PR partial response, MR minor response, SD static disease, PD progressive disease a Tumor size is presented as a percentage of liver volume b Survival at the time of final follow-up is indicated in bold and italic font via the hepatic left or right artery, and ten via the hepatic proper artery.…”
Section: Interventional Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Embolization alone is an effective treatment, but application of gel foam can be used to enforce treatment efficacy. 8 Therefore, when rich blood supplies were observed following infusion, 1×1-mm gel foam granules were used during the embolization. Six patients were embolized via hepatic segmental artery, nine Large mass diameter of a single tumor >5 cm, nodules diameter of a single tumor <5 cm, diffuse diameter of a single tumor <3 cm with multiple tumors, PR partial response, MR minor response, SD static disease, PD progressive disease a Tumor size is presented as a percentage of liver volume b Survival at the time of final follow-up is indicated in bold and italic font via the hepatic left or right artery, and ten via the hepatic proper artery.…”
Section: Interventional Therapymentioning
confidence: 99%
“…2,3 This approach is particularly applicable to hepatic tumors, since the tumor blood supply is primarily derived from the hepatic artery, whereas normal liver tissue is predominantly supplied with blood through the portal vein. [4][5][6][7][8] A recent review concluded that radioembolization with 90-yttrium glass microspheres for the treatment of patients with advanced hepatocellular carcinoma resulted in significant antitumor effects and that this promising new approach for targeted radiation delivery could effectively ameliorate this malignancy. 9 Similar to external radiotherapy, the therapeutic response of patients receiving internal radiation is closely related to the absorption of radiation doses within the tumor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, this radioisotope was mainly used for the therapy of bone pain and metastases, in ovarian cancer and for myeloproliferative diseases (Pattillo et al 1995;Berlin 2000;PanditTaskar et al 2004;Tennvall & Brans 2007). More recently, studies on the use of 32 P as colloid or microsphere for solid tumors were performed; they showed not only an improvement in the patient's quality of life, but also in their survival (Gao et al 2008;Wang et al 2008). However, 32 P was not used in RIT due to the difficulty of the radiolabeling.…”
Section: Introductionmentioning
confidence: 99%